Screening of Chemical Libraries for New Antifungal Drugs against Aspergillus fumigatus Reveals Sphingolipids Are Involved in the Mechanism of Action of Miltefosine - Thaila Fernanda dos Reis (American Society for Microbiology, 2021)
ABSTRACT Aspergillus fumigatus is an important fungal pathogen and the main etiological agent of aspergillosis, a disease characterized by a noninvasive process that can evolve to a more severe clinical manifestation, called invasive pulmonary aspergillosis (IPA), in immunocompromised patients. The antifungal arsenal to threat aspergillosis is very restricted. Azoles are the main therapeutic approach to control IPA, but the emergence of azole-resistant A. fumigatus isolates has significantly increased over recent decades. Therefore, new strategies are necessary to combat aspergillosis, and drug repurposing has emerged as an efficient and alternative approach for identifying new antifungal drugs. Here, we used a screening approach to analyze A. fumigatus in vitro susceptibility to 1,127 compounds. A. fumigatus was susceptible to 10 compounds, including miltefosine, a drug that displayed fungicidal activity against A. fumigatus. By screening an A. fumigatus transcription factor null library, we identified a single mutant, which has the smiA (sensitive to miltefosine) gene deleted, conferring a phenotype of susceptibility to miltefosine. The transcriptional profiling (RNA-seq) of the wild-type and ΔsmiA strains and chromatin immunoprecipitation coupled to next-generation sequencing (ChIP-Seq) of an SmiA-tagged strain exposed to miltefosine revealed genes of the sphingolipid pathway that are directly or indirectly regulated by SmiA. Sphingolipid analysis demonstrated that the mutant has overall decreased levels of sphingolipids when growing in the presence of miltefosine. The identification of SmiA represents the first genetic element described and characterized that plays a direct role in miltefosine response in fungi. IMPORTANCE The filamentous fungus Aspergillus fumigatus causes a group of diseases named aspergillosis, and their development occurs after the inhalation of conidia dispersed in the environment. Very few classes of antifungal drugs are available for aspergillosis treatment, e.g., azoles, but the emergence of global resistance to azoles in A. fumigatus clinical isolates has increased over recent decades. Repositioning or repurposing drugs already available on the market is an interesting and faster opportunity for the identification of novel antifungal agents. By using a repurposing strategy, we identified 10 different compounds that impact A. fumigatus survival. One of these compounds, miltefosine, demonstrated fungicidal activity against A. fumigatus. The mechanism of action of miltefosine is unknown, and, aiming to get more insights about it, we identified a transcription factor, SmiA (sensitive to miltefosine), important for miltefosine resistance. Our results suggest that miltefosine displays antifungal activity against A. fumigatus, interfering in sphingolipid biosynthesis.